The induced hepatotoxicity and genotoxicity in Oreochromis niloticus exposed to a newly released florpyrauxifen-benzyl herbicide - Noura Nabet; Elsayed A. Khallaf; Alaa Alne-na-ei; Islam M. El-Garawani; Rehab G. Elgendy; Esraa Hanafy; Nasr Khalil; Heba M. R. Hathout (Ecotoxicology, 2025)
The investigation of the toxic potential of a newly introduced herbicide, Florpyrauxifen-benzyl (FPX), on Nile tilapia ( Oreochromis niloticus ) was the aim of this study. For 96 h, the median lethal concentration (LC 50 ) was assessed in fish juveniles using the Probit analysis following the exposure to five concentrations of FPX (2–3 ppm). For investigating some mechanisms of FPX toxicity, fish were allocated into three groups (0, 0.27 and 0.54 ppm of FPX) and the cut-off intervals of the exposure were at 7 and 15 days. Liver malondialdehyde (MDA) and reduced glutathione (GSH) levels were assessed. In addition, superoxide dismutase (SOD) and catalase (CAT) were evaluated at both of transcriptional and enzymatic activity levels. Histopathological effects on the liver and erythrocytic nuclear abnormalities (ENAs) were monitored too. The 96h-LC 50 was found to be 2.61 ppm, revealing the toxic potential of the FPX on Nile tilapia. Concentrations of FPX induced oxidative stress in fish by altering activities of antioxidant enzymes and their transcripts. The genotoxic effect of FPX was evidenced by a significant ( P < 0.05) increase in micronuclei (MNs) and ENA frequencies. Significant liver histopathological alterations were observed at both FPX concentrations, with the highest effects at a concentration of 0.54 ppm FPX. Results suggest that FPX may exert oxidative, genotoxic, and histopathological effects on non-targeted species such as Nile tilapia if it is used improperly. Although fish could be used as an indicator for toxic materials in the aquatic habitat, future studies on other organisms, FPX concentrations or durations are recommended.